Cardiac Infections: Understanding Pathophysiology, Diagnosis, and Treatment Strategies - Mathew, Sandra Rose; Soman, Sauparnika; V.U, Risana.; S. S, Kiron. (Current Patterns and Factors Associated with Infectious Diseases, 2024)
Cardiac infections encompass a wide range of microbial pathogens and clinical presentations, and together they represent a diverse spectrum of conditions that affect the cardiovascular system. A concise but thorough review of the etiology, pathophysiology, diagnosis, and treatment of cardiac infections is given in this chapter. Initially, the chapter lists the different infectious agents that are associated with heart infections, with a focus on bacterial, viral, fungal, and parasitic causes. Then we discuss the complex pathophysiological mechanisms, their clinical manifestations, and available therapeutic interventions. By providing a deeper understanding of cardiac infections and supporting the creation of efficient management strategies, this overview hopes to be a useful tool for researchers and clinicians working to enhance patient care and outcomes.